The Improvement of Student Competency in a Clinical Study in Indonesia: What Factors Played an Important Role? - Muhammad Hadi; Achir Yani S Hamid; Sudijanto Kamso; Sutoto Sutoto; Ahmad Watik Pratiknya; Nursalam Nursalam; Ferry Efendi (Universitas Airlangga, 2017)
Background: The improvement of nursing student competency currently is still being an issue for the majority of nursing education institutions in Indonesia. This is due to partnership with hospitals has not been supported by adequate policies and other factors.Objectives: The purpose of this study was to identify the appropriate model in improving student competency in a clinical study. Design used in this study was observational study with cross-sectional approach.Methods: The research design used cross-sectional approach with involving five hospitals (Fatmawati Jakarta Hospital, Hasan Sadikin Bandung Hospital, Kariadi Semarang Hospital, Sardjito Yogyakarta Hospital, Soetomo Surabaya Hospital) and five universities namely Muhammadiyah Jakarta University, Padjajaran Bandung University, Gadjah Mada Jogjakarta University, Diponegoro Semarang University, Airlangga Surabaya University. Three hundred and eighty-four participants were recruited from these sites. Data were analyzed using multiple logistic regression.Results: The result showed that partnership contributed 3,36 times, the patient variations 2,96 times, job description of clinical educator 2,30 times, a role model 2,28 times, expertise of faculty educator 2,08 times, toward the achievement of student competency in clinical study.Conclusions: It can be concluded that partnership aspect, the patient variation, job description of clinical educator, role model, expertise of faculty educator, and level of education have significant role to improve the achievement of student competency in clinical study. The results of this study can be used by nursing educational institutions, hospitals and government to organize nursing education model that has been present for more optimal achievement of student competencies.